2019
DOI: 10.33137/ijidi.v3i3.32964
|View full text |Cite
|
Sign up to set email alerts
|

Work Experiences, Accommodations, and Information in the Context of Fibromyalgia: A Literature Review and Conceptual Synthesis

Abstract: This paper explores the challenges that individuals with fibromyalgia may experience in navigating the workplace. Fibromyalgia is a syndrome characterized by chronic widespread pain, stiffness, sleep disruption, and other symptoms, without a well-defined underlying disease. At work, patients can struggle with various problems, including fluctuating symptoms, exhaustion, skepticism, questions about whether to disclose, and finding ways to adjust work situations. Individuals often lack information concerning how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(112 reference statements)
1
1
0
Order By: Relevance
“…Although the primary etiology of FM syndrome is still unknown, and predisposing factors are a topic of debate, the disease has been generally diagnosed, treated, and cared for by rheumatologists (20,21). In our study, the overall prevalence rate of FM in the participants was approximately 35% by clinicians' (4,23,24). However, as demonstrated by our study and the existing literature, there are still obscurities in the diagnosis of patients with FM, decreasing the rate of agreement between criteria and physician's judgment (25,26).…”
Section: Discussionsupporting
confidence: 54%
“…Although the primary etiology of FM syndrome is still unknown, and predisposing factors are a topic of debate, the disease has been generally diagnosed, treated, and cared for by rheumatologists (20,21). In our study, the overall prevalence rate of FM in the participants was approximately 35% by clinicians' (4,23,24). However, as demonstrated by our study and the existing literature, there are still obscurities in the diagnosis of patients with FM, decreasing the rate of agreement between criteria and physician's judgment (25,26).…”
Section: Discussionsupporting
confidence: 54%
“…However, research also identifies other factors not captured in the RA‐WIS impacting work instability in FM. These include the negative impact of FM on occupational identity (Chen et al., 2019; Depelteau et al., 2021; Mukhida et al., 2020); motivation at work (Arnold et al., 2008); reduced social support from friends, and strained relationships at work (Depelteau et al., 2021; Mukhida et al., 2020); as well as concerns about disclosing their condition at work and social stigma associated with FM from colleagues and supervisors (Mukhida et al., 2020). A recent study identified that FM‐related sick leave was not directly related to the condition itself, but rather issues such as commute time, repetitive work movements, work difficulties, job stress, noisy workplaces, limited career progression, and lack of recognition or understanding of FM by managers and co‐workers (Laroche et al., 2019).…”
Section: Discussionmentioning
confidence: 99%